From contact coverage to effective coverage of community care for patients with severe mental disorders: A real-world investigation from Italy - Corrao, Giovanni; Monzio Compagnoni, Matteo; Barbato, Angelo; D’Avanzo, Barbara; Di Fiandra, Teresa; Ferrara, Lucia; Gaddini, Andrea; Saponaro, Alessio; Scondotto, Salvatore; Tozzi, Valeria D.; Carle, Flavia; Carbone, Simona; et al. (Frontiers in Psychiatry, 2022)
Objectives To measure the gap between contact and effective coverage of mental healthcare (MHC). Materials and methods 45,761 newly referred cases of depression, schizophrenia, bipolar disorder, and personality disorder from four Italian regions were included. A variant of the self-controlled case series method was adopted to estimate the incidence rate ratio (IRR) for the relationship between exposure (i.e., use of different types of MHC such as pharmacotherapy, generic contact with the outpatient services, psychosocial intervention, and psychotherapy) and relapse (emergency hospital admissions for mental illness). Results 11,500 relapses occurred. Relapse risk was reduced during periods covered by (i) psychotherapy for patients with depression (IRR 0.67; 95% CI: 0.49 to 0.91) and bipolar disorder (0.64; 0.29 to 0.99); (ii) psychosocial interventions for those with depression (0.74; 0.56 to 0.98), schizophrenia (0.83; 0.68 to 0.99), and bipolar disorder (0.55; 0.36 to 0.84), (iii) pharmacotherapy for patients with schizophrenia (0.58; 0.49 to 0.69), and bipolar disorder (0.59; 0.44 to 0.78). Coverage with generic care, in absence of psychosocial/psychotherapeutic interventions, did not affect risk of relapse. Conclusion This study ascertained the gap between contact and effective coverage of MHC and showed that administrative data can usefully contribute to assess the effectiveness of a mental health system.